2003
DOI: 10.1179/030192303225004097
|View full text |Cite
|
Sign up to set email alerts
|

Structure-property changes during hardening and tempering of new ultra high strength medium carbon low alloy steel

Abstract: not desirable, while an increase in the carbon level in conventional processing severely aVects the ductility, fracture A medium carbon low alloy steel, electroslag toughness and weldability of such a class of steel. 2 refined, modified AFNOR 15CDV6, has been Electroslag re ning (ESR) processing has provided an developed for satellite launch vehicle and alternative. 5-8 The ESR processed, with suitable inoculation, related applications. Conventionally processed ascast 15CDV6 alloy showed a 40% improvement in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…The combined effects of the above in association with fine grain structure contribute greatly to enhanced resistance of the steel tempered at 473 K. At higher tempering temperatures, in 0?3C-CrMoV (ESR) steel, the e-carbides are converted into relatively thick cementite platelets of the same morphology along the lath boundaries as well as within the laths. 20 At and above 723 K, relatively recovered regions of microstructure having nearly parallel lath morphology with equiaxed shape are also observed (Fig. 10).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The combined effects of the above in association with fine grain structure contribute greatly to enhanced resistance of the steel tempered at 473 K. At higher tempering temperatures, in 0?3C-CrMoV (ESR) steel, the e-carbides are converted into relatively thick cementite platelets of the same morphology along the lath boundaries as well as within the laths. 20 At and above 723 K, relatively recovered regions of microstructure having nearly parallel lath morphology with equiaxed shape are also observed (Fig. 10).…”
Section: Discussionmentioning
confidence: 86%
“…The presence of retained austenite was observed in a few cases during transmission electron microscopy studies of the steel in the as hardened condition (Fig. 7) as well as in specimens tempered at up to 573 K. 20 This retained austenite was heavily dislocated and rarely exceeded 100-200 nm in size, and disappeared on tempering above 573 K. Fine rodlike precipitates started precipitating out on tempering at low temperatures up to 423 K, and were identified as mostly hexagonal e-carbide by electron diffraction (Fig. 8).…”
Section: Discussionmentioning
confidence: 90%
“…Tempering in the range of 100-200uC in fact increases the yield strength due to incipient carbide precipitation. Suresh et al 13 found such an increase in strength on tempering oil quenched samples of 0 . 30CrMoV (ESR) steel.…”
Section: Properties Of Cooled Platesmentioning
confidence: 95%
“…Many alloys for critical application now use this process to ensure reliability and good properties. The material developed earlier at Indian Institute of Technology (IIT) Bombay and Vikram Saravai Space Center (VSSC), Trivandrum, India with a yield strength of 1450 MPa, is qualified as aerospace application (Suresh et al, 2003;Chatterjee et al, 1990). This was a medium-carbon low alloy steel used mostly in tempered condition.…”
Section: Issues and Objectivementioning
confidence: 99%
“…This was a medium-carbon low alloy steel used mostly in tempered condition. The chemical composition of the alloy is: 0.3% C, 1.0% Mn, 1.0% Mo, 1.5% Cr, 0.3% V and named as 0.3C-CrMoV (ESR) steel (Suresh et al, 2003). The microstructure of heat treated alloy primarily consists of tempered lath martensite.…”
Section: Issues and Objectivementioning
confidence: 99%